COMPARISON OF INTEREST IN ENTERING UNIVERSITY - BEFORE AND AFTER THE COVID-19 - ON STUDENT OF AUTOMOTIVE ENGINEERING IN SMK NEGERI 1 KOTO XI TARUSAN - Rinaldo, Afriko; Erizon, Nelvi; Yufrizal, Yufrizal; Primawati, Primawati (Universitas Pendidikan Indonesia, 2022)
The interest of a student to enter college must be different according to his personality. This is influenced by the knowledge gained by students; therefore, it is important to provide knowledge about the college. The purpose of this study was to determine the comparison of student interest in entering college before and after the COVID-19 pandemic. The type of research used in this study is descriptive with a quantitative approach. The population of this research is students of the Department of Automotive Engineering at SMK N 1 Koto XI Tarusan academic year 202012022 with a sample of students in class X XII majoring in automotive engineering at SMK N 1 Koto XI Tarusan the number of students is 49 research samples. The results of the research conducted using the t-test, and the t-test results obtained with a value of sig(2-tailed) 0.00 which means it is smaller than 0.005, therefore the results of the t-test indicate that there is a difference in the interest in entering college in automotive engineering college students. SMK N 1 Koto XI Tarusan before and after COVID-19. From this research, it can be concluded that the interest in entering college at college of students majoring in automotive engineering at SMK N 1 Koto XI Tarusan before and after COVID-19 there is a significant difference, this is influenced by the circumstances experienced by these students at this time, namely the COVID-19 pandemic.